2011
DOI: 10.4314/bajopas.v2i2.63764
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary phytochemical and antimicrobial screening of they stem bark extracts of <i>Bauhinia rufescence</i> Lam using some selected pathogens

Abstract: Bauhinia rufescens Lam (Leguminosea-Caesalpinoideae) stem bark was extracted using methanol and fractionated using ethylacetate, butanol and water. The extract and fractions were subjected to preliminary phytochemical screening using standard procedures followed by antimicrobial screening using disc diffusion and broth dilution techniques. The extract and fractions showed the presence of carbohydrate, tannins, flavonoids, saponins, terpenes and steroids. The antimicrobial screening of the extract and fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, the leaf extract showed higher antibacterial and antifungal activity against the microbes than the stem extract. This according to Hassan et al (2009) could be attributed to presence of higher bioactive compounds in leaf extracts. Furthermore, the sensitivity and susceptibility of the microbes to the plant extracts varied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the leaf extract showed higher antibacterial and antifungal activity against the microbes than the stem extract. This according to Hassan et al (2009) could be attributed to presence of higher bioactive compounds in leaf extracts. Furthermore, the sensitivity and susceptibility of the microbes to the plant extracts varied.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf extract showed higher antimicrobial activity against the microbes than the stem extract. This according to Hassan et al (2009), could be attributed to presence of higher bioactive compounds in leaf extracts. Furthermore, the sensitivity and susceptibility of the microbes to the plant extracts varied.…”
Section: Resultsmentioning
confidence: 98%
“…From the study, the leaf showed significantly higher inhibitory effects against the tested pathogens when compared to root and stem extracts. According to [21] this could be attributed to presence of higher bioactive compounds in the leaf extract than in the stem and root extracts. The result revealed inhibitory effect of the extracts against the pathogens to be in direct proportion to the concentration of the extracts (i.e.…”
Section: Resultsmentioning
confidence: 99%